Domains, competences and learning outcomes for undergraduate education in periodontology - Figuero, Elena (Wiley-Blackwell, 2025)
Aim: This review is intended to adapt the current conceptual framework in dental education based on four domains to propose a set of competences, learning outcomes and methods of teaching, learning and assessment for undergraduate education in periodontology.
Review: Based on the current framework of competences and learning outcomes recommended by the Association for Dental Education in Europe (ADEE), undergraduate education in periodontology has been updated using the classification and clinical practice guidelines for the diagnosis and treatment of periodontal and peri-implant diseases.
Conclusions: Specific learning outcomes have been proposed within each competence area, that is in Domain I (n = 10), Domain II (n = 13), Domain III (n = 33) and Domain IV (n = 12). Teaching methods and learning activities based on the different dimensions of the cognitive process have been proposed. Additionally, 10 key learning outcomes have been proposed as exit outcomes, which implies their accomplishment within the final assessment of any graduating student.